2016
DOI: 10.4103/0028-3886.185352
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic pituitary surgery: Techniques, tips and tricks, nuances, and complication avoidance

Abstract: Endoscopic pituitary surgery is useful in all micro- and macro-pituitary adenomas including those with suprasellar and cavernous sinus extension. The endoscope provides a panoramic close-up, a multi-angled view with excellent illumination and magnification, permitting complete excision of the tumor with preservation of normal pituitary. However, surgeons need to learn altogether different skills unique to endoscopy and the learning curve is steep. The learning curve can be shortened by proper selection of case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Patients with a nonfunctioning adenoma confined to sella in a well-pneumatized sphenoid sinus are the best cases. [6] Preoperative planning with meticulous study of MRI and CT of the patient is of paramount importance. Sphenoid sinus anatomy is specific for each individual like as is the case with finger prints.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with a nonfunctioning adenoma confined to sella in a well-pneumatized sphenoid sinus are the best cases. [6] Preoperative planning with meticulous study of MRI and CT of the patient is of paramount importance. Sphenoid sinus anatomy is specific for each individual like as is the case with finger prints.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] The benefits of endoscope are tangible, however, there are certain disadvantages such as two-dimensional view, limited zoom and focus capability, and the need for two surgeons. [6] More importantly, shifting from microscope to endoscope needs a different set of skills. In this series, we present our experience during the first 83 cases and the lessons learned during this journey.…”
Section: Introductionmentioning
confidence: 99%
“…The principal major complications anticipated are vascular injury and orbital and intracranial complications which vary from 1 to 3% ( Table 2). The most frequent immediate complications are CSF leak, intraoperative bleeding, orbital hematoma and injury to brain (27,28). Delayed complications include progressive loss of vision (24) or smell, meningitis, bleeding, synechiae, and infection.…”
Section: Discussionmentioning
confidence: 99%
“…These can be divided into two major categories: (1) Nonendocrinal; and, (2) endocrinal complications- (27,28) (Table 1).…”
Section: Complications and Their Avoidancementioning
confidence: 99%
“…This technique has the advantages of clear visual field, less blind area, less trauma, flexible observation angle, high total tumor resection rate, rapid recovery after surgery, and others. The endoscopic endonasal approach (EEA) has become the main surgical method for resection of pituitary adenomas [14]. Its excellent postoperative results have shown that this surgical procedure is effective not only for saddle adenomas but also for the giant pituitary adenomas invading the suprasellar region.…”
Section: Introductionmentioning
confidence: 99%